One nuclear calcium transient induced by a single burst of action potentials represents the minimum signal strength in activity-dependent transcription in hippocampal neurons - Yu, Yan; Oberländer, Kristin; Bengtson, C. Peter; Bading, Hilmar (Cell calcium, 2017)
Neurons undergo dramatic changes in their gene expression profiles in response to synaptic stimulation. The coupling of neuronal excitation to gene transcription is well studied and is mediated by signaling pathways activated by cytoplasmic and nuclear calcium transients. Despite this, the minimum synaptic activity required to induce gene expression remains unknown. To address this, we used cultured hippocampal neurons and cellular compartment analysis of temporal activity by fluorescence in situ hybridization (catFISH) that allows detection of nascent transcripts in the cell nucleus. We found that a single burst of action potentials, consisting of 24.4±5.1 action potentials during a 6.7±1.9s depolarization of 19.5±2.0mV causing a 9.3±0.9s somatic calcium transient, is sufficient to activate transcription of the immediate early gene arc (also known as Arg3.1). The total arc mRNA yield produced after a single burst-induced nuclear calcium transient was very small and, compared to unstimulated control neurons, did not lead to a significant increase in arc mRNA levels measured using quantitative reverse transcriptase PCR (qRT-PCR) of cell lysates. Significantly increased arc mRNA levels became detectable in hippocampal neurons that had undergone 5-8 consecutive burst-induced nuclear calcium transients at 0.05-0.15Hz. These results indicate that a single burst-induced nuclear calcium transient can activate gene expression and that transcription is rapidly shut off after synaptic stimulation has ceased.